Evaluation of Salivary ?- Amylase Enzyme Activity in Smoker and Peptic Ulcer Patients affected by Periodontitis in Relation to Clinical Periodontal Parameters - Nada Kadhim Imran1 , Omar Husham Ali1 , Maha Abdulaziz Ahmed1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: To investigate the activity of salivary ?-amylase (SA) in subject affected by periodontitis aloneor associated with peptic ulcer disease (PUD) with or without smoking.Methods: The study population was divided into control group (C), study groups; periodontitis (G1),periodontitis+ PUD+ smokers (G2), periodontitis+ PUD+ nonsmoker (G3). The clinical periodontalparameters including plaque index (PI), gingival index (GI), probing pocket depth (PPD), and clinicalattachment level (CAL) were recorded.In addition, unstimulated whole saliva was collected from thesepatients for analysis of SA level.Results: Analysis showed that PI and GI showed significant difference among study groups versus controls.G2 exhibited significantly higher PPD and CAL as compared with G1 but not with G3. For SA activity, G2and G3 showed significantly higher activity as compared with C and G1 groups. Yet, no significant differencewas seen between C and G1 and between G2 and G3. Activity of SA was positively and significantly (P<0.05) correlated with increasing PPD in all study groups and with CAL measurements of G2 only.Conclusions: The results suggested that SA could be used as a marker for the diagnosis of PUD in subjectsaffected by periodontitis with or without smoking.